Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning pada Submateri Perkembangbiakan Tumbuhan - Setiyawati, Neni; Panjaitan, Ruqiah Ganda Putri; Wartiningsih, Wartiningsih (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research aims to improve student learning outcomes through the application of the discovery learning model to the sub-material of plant reproduction. The type of research used is collaborative classroom action research. The research was carried out in 2 cycles consisting of planning, implementation, observation and reflection. The subjects in this research were students in class IX F of SMP Negeri 12 Pontianak, consisting of 32 people. Data were collected using observation sheets on learning implementation and evaluation questions consisting of 10 description questions. The results of the research show that the application of the discovery learning model can improve student learning outcomes, namely in cycle 1 the number of students who got a passing grade was 16 people with a percentage of 50% and experienced an increase in cycle 2, namely the number of students who got a passing grade became 23 people with a percentage of 71.87%. It can be concluded that the application of the discovery learning model to the sub-material of plant reproduction can improve the learning outcomes of class IX F students at SMP Negeri 12 Pontianak.